Penerapan Model Pembelajaran Problem Based Learning (PBL) Terhadap Hasil Belajar Peserta Didik Pada Materi AlQur’an Kelas X SMK Negeri 1 Silaut Tahun Pelajaran 2024/2025 - Marjono, Adil (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to analyze the implementation of the Problem-Based Learning (PBL) model in improving students’ learning outcomes in Islamic Religious Education (PAI). The research employed a classroom action research design consisting of two cycles, each involving planning, implementation, observation, and reflection. The results of the study indicate that the application of the PBL model improved both teacher and student activities, as well as student learning outcomes. In Cycle II, teacher activity increased from 79.3% to 86.5%, while student activity reached an average of 82.5%. Student learning outcomes also showed significant improvement, with an average posttest score of 85. In conclusion, the PBL model is effective in enhancing the quality of learning and student learning outcomes.